Gender differences in the relationship between religiosity and health-related behaviour among adolescents. Issue 12 (8th May 2012) - Pitel, Lukas; Madarasova Geckova, Andrea; Kolarcik, Peter; Halama, Peter; Reijneveld, Sijmen A; van Dijk, Jitse P
Abstract : Background: An inverse relationship between religiosity and adolescent health-related behaviour has been repeatedly documented, but evidence regarding gender is scarce. The aim of this study was to assess the association between a wide range of adolescent health-related behaviours and religiosity as well as gender differences in these associations. Methods: Data were collected in 2010 in Slovakia on 3674 adolescents, with mean age of 14.9 years (response: 79.5%). ORs for levels of religiosity, measured by religious attendance and religious salience, were calculated for 15 behaviours, such as the use of various substances, nutritional behaviour and violent behaviour. The authors then assessed the interactions of religiosity and gender on these behaviours. Results: Religiosity was inversely associated with health–risk behaviour in smoking, drunkenness, cannabis use, having breakfast, soft drinks consumption, screen-based activities and sexual intercourse among both genders and in truancy among girls only. This association was significantly stronger among girls than among boys in smoking, drunkenness and cannabis use. Religiosity was unrelated to the consumption of fruits, vegetables and sweets, physical inactivity, tooth brushing, fighting and bullying others in both genders. Conclusions: An inverse relationship between religiosity and health–risk behaviour was found in several behaviours (especially use of substances) but not in other behaviours (violent behaviours in particular). Gender seems to moderate this relationship in smoking, drunkenness and cannabis use. Further research is needed on the mechanisms leading to an association between religiosity and health behaviour and on the strength of this association in other countries and cultures.